AN ANALYSIS DEIXIS IN RIDWAN KAMIL’S SPEECH AT THE ASIA AFRICA CONFERENCE (KAA) - Aas Asmarita; Acep Haryudin (PROJECT (Professional Journal of English Education), 2019)
The central topics of pragmatics, this study is limited on applying deixis on speech Ridwan Kamil at the Asia Africa Conference (KAA). This research deals with the English deixis. The objectives of this study are to analyze type of deixis and to find out the most dominant type of deixis in “Ridwan Kamil’s speech  at Asia Africa Conference (KAA)” on April 24th 2015. This study was conducted by using qualitative approach. From the five type of deixis, in Ridwan Kamil’s speech found that there are three types of deixis, namely person deixis (7 data) time deixis (3 data), and the last is social deixis (1 data). From the analysis of deixis, it was also revealed that person deixis as the most dominant type which was found on speech Ridwan Kamil at the Asia Africa Conference. Keywords:  Deixis, Asia Africa Conference (KAA), Speech